Circulation and reception of the theory of "academic capitalism" in Latin America - José Joaquín Brunner; Julio Labrana; Francisco Ganga; Emilio Rodríguez-Ponce (Arizona State University, 2019)
In recent decades, the theory of academic capitalism has gained increasing relevance as an approach for understanding the recent evolution of higher education systems. We analyze the reception of academic capitalism theory in Latin America. To meet this objective, the conceptual underpinnings of academic capitalism are explored as well as their criticisms in the specialized literature. Next, the Latin-American reception of this conceptual approach is examined in detail, with special attention to the ways in which this approach is used to evaluate national higher education systems. Building upon this analysis, it is argued that the Latin-American reception process shows limitations both in quantitative and qualitative terms and is frequently used to criticize the state of higher education systems rather than to understand them. The article closes with a summary and selected future lines of research.